An experimental analysis on performance of tobacco seed oil as an alternative fuel for diesel engine - Balaji Ramachandran; Ravikumar Solomon; Pardeep Sangwan; C. Edwin Samuel; Unai Fernandez-Gamiz; Shyam Sundar Santra; Mohamed Altanji; Vediyappan Govindan (Alexandria Engineering Journal, 2023)
Biodiesel replaced imported oils as an ecologically beneficial alternative which may replace diesel depending on crop and oil costs. Tobacco seed oil is trans-esterified using a heterogeneous base catalyst to produce biodiesel in this study to examine the mechanical properties and emission performance characteristics using single-cylinder Kirloskar engine. Several biofuel/diesel blends were tested, and their effects on performance and efficiency were examined under varying loads at a constant rotational speed of 1500 rpm. The engine's performance and emissions characteristics were measured and compared at a fuel injection pressure of 200 bar. The results of the experimental studies show that the tobacco seed oil and biodiesel blends are more efficient than diesel fuel and their blend ratios that boost brake thermal efficiency by 10.27%, 16.66%, 9.23%, and 11.87% under 25%, 50%, 75%, and 100% of loading, respectively, outperform other biodiesel blends with significant environmentally sustainable emission characteristics.